Three Essays on Refining the Challenge and Hindrance Stressors Framework - (:unkn) unknown (My University, 2014)
Job demands, or stressors, are viewed as "physical, psychological, social, or organizational aspects of the job that require sustained physical and/or psychological effort" (Bakker & Demerouti, 2007) and are traditionally seen as detrimental due to their influence on stress. However, recent advancements suggest that, despite their effect on stress, some demands (i.e., challenge demands) could be instrumental in achieving valued personal and job outcomes, while others (i.e., hindrance demands) would have purely deleterious effects (Cavanaugh, Boswell, Roehling, & Boudreau, 2000). Based on this challenge and hindrance stressors framework, scholars have found differentiated effects of demands in relation to outcomes such as job performance, job satisfaction, and turnover (e.g., LePine, Podsakoff, & LePine, 2005; Podsakoff, LePine, & LePine, 2007). Despite the extensive contribution of the challenge and hindrance stressors framework, the notion that some demands can be beneficial is relatively recent and more research is needed to fully elucidate the nature of stressors. Thus the first purpose of this three-essay dissertation is to identify the important questions that still need to be answered in regard to job demands. The second goal is to examine some of the most pressing issues and begin to refine the challenge and hindrance stressors framework. The first essay represents a comprehensive review of research on job demands. I focus on clarifying specific rather than composite job demands that differ in terms of the extent to which they are deleterious and beneficial in association with desirable work outcomes. While some job demands are clearly deleterious or beneficial, several demands emerged as having mixed effects on work outcomes. That is, this `middle of the continuum' group of job demands tends to have contradictory effects across various studies. To understand these variations in empirical findings, I look at the role of contextual and personal contingencies. The second study is focused on the short-term daily effects of job demands and the interplay between anticipated and unanticipated stressors to examine the daily situational context within which demands occur. Based on Mandler's (1975) theory of interruptions I suggest that unanticipated demands in an already challenging situation would be seen as detrimental by employees despite the fact that in normal circumstances some of these demands would be seen as beneficial. To empirically examine this, I use a daily diary study approach. The results, however, do not find strong support for Mandler's (1975) theory. The purpose of the third essay is to expand the challenge and hindrance stressors framework to the context of global employees, in particular to better understand the experiences of international business travelers (IBTs). Drawing on an integration of role theory (Kahn, Wolfe, Quinn, Snoek, & Rosenthal, 1964; Katz & Kahn, 1978) and the challenge and hindrance stressors framework I propose and test a theoretical model where IBTs' adjustment and subsequent career satisfaction is affected positively or negatively, depending on the types of demands experienced as part of IBTs' participation in work and family roles. Through conducting a two-wave study of IBTs, I find general support for the proposed model of the differentiated effects of work and family challenge and hindrance demands on IBTs' adjustment and career satisfaction . The work role, however, was ultimately found to have a stronger influence on IBTs' subsequent career satisfaction than the family role. Since stressors are a vital part of employees' experiences and an essential building block of management theories, it is necessary to better understand their nature and effects. This dissertation contributes to the literature by (1) offering a clear synthesis of the differentiated effects of work demands, (2) contributing to our understanding of how demands influence employees on a day-to-day basis, and (3) elucidating the effects of work and family demands in the context of international business travel.
Keywords: Challenge and Hindrance Demands; International Business Travelers; Job Demands; Role Theory; Stressors